The Utilization of Inert Materials for the Control of Stored-Product Mites—A Mini Review - Christos G. Athanassiou; Christos I. Rumbos; Paraskevi Agrafioti; Maria K. Sakka (Insects)
Stored-product mites are important pests of stored products, while their presence in storage and processing facilities has a significant effect on public health. On the other hand, inert materials are promising alternatives to conventional pesticides in stored product protection and have provided very good results against storage insects. These formulations can be applied either directly on the product or on surfaces, as dusts or as slurry formulations. In the current paper, we review the factors that affect the efficacy of inert dusts, emphasizing in diatomaceous earths, against stored-product mites. Hence, we address the different biotic and abiotic factors that affect the acaricidal effect of inert materials against different mite species, but also the complexity of such an application, that often arises from the simultaneous presence of plant-feeding mites with their mite predators. Finally, we provide some insights for further research directions.